A Method for Producing Highly Pure Magnetosomes in Large Quantity for Medical Applications Using Magnetospirillum gryphiswaldense MSR-1 Magnetotactic Bacteria Amplified in Minimal Growth Media - Berny, Clément; Le Fèvre, Raphael; Guyot, François; Blondeau, Karine; Guizonne, Christine; Rousseau, Emilie; Bayan, Nicolas; Alphandéry, Edouard (Frontiers in Bioengineering and Biotechnology, 2020)
We report the synthesis in large quantity of highly pure magnetosomes for medical applications. For that, magnetosomes were produced by MSR-1 Magnetospirillum gryphiswaldense magnetotactic bacteria using various minimal growth media devoid of uncharacterized and toxic products prohibited by pharmaceutical regulation, i.e. yeast extract, heavy metals different from iron, and carcinogenic, mutagenic and reprotoxic agents. This method follows two steps, during which bacteria were first pre-amplified without producing magnetosomes and were then fed with an iron source to synthesize magnetosomes, yielding, after 50 hours of growth, an equivalent OD565 of 8 and 10 mg of magnetosomes in iron per liter of growth media. Compared with magnetosomes produced in non-minimal growth media, those particles had lower concentrations in metals other than iron. Very significant reduction or disappearance in magnetosome composition of zinc, manganese, barium, and aluminum were observed. This new synthesis method paves the way to the production of magnetosome production for medical applications.